1986
DOI: 10.1139/y86-074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17β-estradiol on myometrial gap junctions and pregnancy in the rat

Abstract: The effects of estradiol treatment on the development of myometrial gap junctions and premature labour were investigated using timed pregnant rats. In control animals myometrial gap junctions were infrequent between days 17 and 20 of pregnancy, but began to develop on day 21 and were at maximum frequency, size, and membrane area on day 22 during delivery. Gap junctions were completely absent from the myometrium 48 h after delivery. Animals treated with 500 micrograms 17 beta-estradiol/day starting on day 16 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Estrogens are found to be stimulatory to the initiation of labor in animals that experience progesterone withdrawal before parturition (2)(3)(4). In contrast, in animals such as guinea pigs, which do not have pre-parturition progesterone withdrawal, estrogen is inhibitory to the initiation of labor (4).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens are found to be stimulatory to the initiation of labor in animals that experience progesterone withdrawal before parturition (2)(3)(4). In contrast, in animals such as guinea pigs, which do not have pre-parturition progesterone withdrawal, estrogen is inhibitory to the initiation of labor (4).…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone suppresses cx43 gene transcription and inhibits the trafficking of Cx43 protein through the Golgi apparatus (12,16). Estrogen can induce premature cx43 expression and gap junction formation in the myometrium of pregnant animals (14,17). However, cx43 expression only remains high in estrogen-treated myometrial cells if internal uterine pressure is maintained after delivery (10).…”
mentioning
confidence: 99%
“…For example, the treatment of timed-pregnant rats with mifepristone-induced uterine contractility , Doret et al 2005) that leads to delivery (Garfield et al 1987, Shi et al 2003, Doret et al 2005. In addition, we and others have shown that treatment with mifepristone caused an increase in contraction-associated proteins such as CX 43 (Mackenzie & Garfield 1986, Garfield et al 1987, Miyoshi et al 1996 and the OTR (Fang et al 1997) in the myometrium. Finally, delivery induced by mifepristone was shown to occur in a more narrow range of time when compared with the time frame for delivery from spontaneous labor at term (Li et al 2004).…”
Section: Ptb Studiesmentioning
confidence: 86%
“…We propose that COMT activity may help to mediate estrogen-related functions in the myometrium during pregnancy at term. These functions include increases in the levels of factors associated with contractility, such as CX 43 (Mackenzie & Garfield 1986, Verhoeff et al 1986, Oltra et al 2003, oxytocin (Fang et al 1996), and the receptors for oxytocin (Fang et al 1996) or PGs (Dong & Yallampalli 2000). Therefore, treatment with the COMT inhibitor may cause a reduction in one or more of these factors, which in turn could result in the attenuation of uterine contractility induced by mifepristone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation